DNA- Drug Binding and Uric Acid Concentrations Relationship in Renal Failure - Mohsin O. Mohammed (Journal of Global Pharma Technology, 2019)
Kidney diseases are recognised as a significant health problem affecting approximately 188 million peoples in low- and middle-income countries. In this study, investigation of the relationship between DNA and UA concentrations and the interaction of DNA and drug in renal failure patients was studied. DNA was extracted from serum and whole blood by two methods, kit and manual to find the best way, by comparison, the results. Nanodrop and electrical migration technique were used to measure the obtained concentration of DNA. The interaction between DNA and drug (Allopurinol) in the presence of UA was done by using ultraviolet and infrared spectroscopies. The study included 80 healthy and 80 patients samples with chronic renal impairment with ages rang (20-80) of both genders. The result showed a significant increase in the concentration of UA, urea and creatinine in renal failure patients compared to control a significant reduction in DNA concentration in patients with high UA concentration, the DNA extracted by manual method was higher compared to the results of the kit. The type of interference between DNA and Allopurinol is intercalative binding.Keywords: Kidney disease, Allopurinol, DNA, Uric acid and renal failure.